Cerebral cortex and hippocampus neural interaction during vagus nerve stimulation under in vivo large-scale imaging - Xu, Hanyun; Jin, Tingting; Zhang, Rujin; Xie, Hao; Zhuang, Chaowei; Zhang, Yanyang; Kong, Dongsheng; Xiao, Guihua; Yu, Xinguang (Frontiers in Neuroscience, 2023)
Objective: The purpose of this study was to study mechanisms of VNS modulation from a single neuron perspective utilizing a practical observation platform with single neuron resolution and widefield, real-time imaging coupled with an animal model simultaneously exposing the cerebral cortex and the hippocampus. Methods：we utilized the observation platform characterized of widefield of view, real-time imaging, and high spatiotemporal resolution to obtain the neuronal activities in the cerebral cortex and the hippocampus during VNS in awake states and under anesthesia. Results：some neurons in the hippocampus were tightly related to VNS modulation, and varied types of neurons showed distinct responses to VNS modulation. Conclusion: we utilized such an observation platform coupled with a novel animal model to obtain more information on neuron activities in the cerebral cortex and the hippocampus, providing an effective method to further study the mechanisms of therapeutic effects modulated by VNS.